Mapping the pedagogical integration of discovery learning and STEAM in enhancing students’ critical thinking skills: A systematic literature review and bibliometric analysis - Tita Fitriana Sukmawati; Endang Susantini; Raharjo Raharjo; Ali Sabri Ipek (CV. FOUNDAE, 2025)
Background: The development of students’ critical thinking skills has become a central concern in 21st-century education, particularly in response to increasingly complex scientific, technological, and societal challenges. Despite the growing number of studies examining these approaches, existing research remains fragmented, and a comprehensive synthesis that maps research trends, thematic orientations, and theoretical implications is still limited. Aims: This study aims to examine the evolution, distribution, and scholarly significance of research on Discovery Learning and STEAM in enhancing students’ critical thinking skills. Methods: A systematic literature review combined with bibliometric analysis was conducted using the Scopus database. A total of 714 documents published between 2014 and 2025 were initially identified using the keywords “Discovery Learning,” “STEAM,” and “critical thinking.” After applying PRISMA-based inclusion and exclusion criteria, 75 peer-reviewed articles were selected for in-depth analysis. Bibliometric mapping was performed using VOSviewer to examine publication trends, country and institutional contributions, keyword co-occurrence, and thematic networks. Results: The findings reveal a consistent growth in research on both Discovery Learning and STEAM, with a notable increase in publications over the last five years. Discovery Learning is predominantly associated with inquiry, experimentation, and metacognitive regulation, while STEAM emphasizes interdisciplinary integration, creativity, and technology-enhanced problem-solving. The analysis also indicates a strong concentration of studies in developing countries, particularly Indonesia, alongside expanding international contributions. However, limited cross-national collaboration and uneven thematic depth remain evident. Conclusion: This review demonstrates that Discovery Learning and STEAM function as complementary pedagogical frameworks that collectively strengthen students’ critical thinking through inquiry-based, interdisciplinary, and reflective learning processes. Beyond confirming their effectiveness, this study highlights the need for deeper theoretical integration, stronger empirical validation, and more globally collaborative research. By synthesizing research trends and identifying underexplored dimensions, this review provides a robust foundation for advancing sustainability-oriented, context-responsive, and future-ready educational practices.